PELAKSANAAN PROGRAM KAMPUNG IKLIM DI KECAMATAN BANTAN KABUPATEN BENGKALIS - Azika Putri Aidila; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
Implementation of the climate village program in Bantan District, Bengkalis Regency, the Climate Village Program (proklim) has been launched as a national movement for community-based climate change control by the Minister of Environment and Forestry through adaptation and mitigation efforts undertaken by communities in facing or preventing the impact of climate change and contributing to efforts to reduce emissions. the program implemented in Bantan District, Bengkalis Regency experienced problems namely the occurrence of abrasion and damage to mangrove forests. The purpose of this study was to analyze the implementation of the Climate Village Program in Bantan District, Bengkalis Regency and find out the factors that influence the Implementation of the Climate Village Program in Bantan District, Bengkalis Regency. Using the theory concept of Policy Implementation according to Wahab in Tahir (2015: 55). Using qualitative descriptive methods. the type of data used is primary data and secondary data. data collection using observation, interview, documentation. Data analysis used is data reduction, data presentation, and drawing conclusions. The results showed that the implementation of the Climate Village Program in Bantan District, Bengkalis Regency had not run optimally. The factors that influence the implementation of the Village Climate Program in Bantan District, Bengkalis Regency are organizational capabilities, information and support.Keywords: Implementation, Program, Climate Village